2018
DOI: 10.3390/su10010263
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Landscape Stewardship across Europe: Landscape Values, Place Attachment, Awareness, and Personal Responsibility

Abstract: Improved perceptions towards landscape stewardship, at the local level, could help achieve more sustainable futures. However, little research has been done on the dimensions of landscape stewardship underlying such perceptions. Here we look at the perception of landscape values, place attachment, awareness of the adverse consequences human action might have on landscapes, and ascription of personal responsibility across Europe as well as how these dimensions are connected and influenced by personal capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…The adolescents' responses are a direct reflection of this physical separation of urban space and are a clear testament to the increasing focus of activities like sport and shopping in the urban periphery, with the urban core retaining its importance for emotional or aesthetic aspects of the human experience, like historical memory and sense of place and belonging. This finding supports recent calls for broader narratives around cultural heritage that are able to account for these intangible experiences beyond just recreation and tourism (García-Martín et al 2018). Moving away from the idea that "that which has no market value has no value at all" (Díaz-Pacheco and Hewitt 2010) towards new kinds of spatial planning that can accommodate these intangible landscape values is in any case likely to reap wider economic benefits in the long run.…”
Section: Implications For Cultural Heritage and Urban Planningsupporting
confidence: 77%
See 1 more Smart Citation
“…The adolescents' responses are a direct reflection of this physical separation of urban space and are a clear testament to the increasing focus of activities like sport and shopping in the urban periphery, with the urban core retaining its importance for emotional or aesthetic aspects of the human experience, like historical memory and sense of place and belonging. This finding supports recent calls for broader narratives around cultural heritage that are able to account for these intangible experiences beyond just recreation and tourism (García-Martín et al 2018). Moving away from the idea that "that which has no market value has no value at all" (Díaz-Pacheco and Hewitt 2010) towards new kinds of spatial planning that can accommodate these intangible landscape values is in any case likely to reap wider economic benefits in the long run.…”
Section: Implications For Cultural Heritage and Urban Planningsupporting
confidence: 77%
“…There is a vast literature, rooted in disciplines ranging from geography and psychology to economics and ethnography, that tries to conceptualize and evaluate human perception of and relation to nature and landscapes. This is pursued, for instance, in terms of sense of place (Jorgensen and Steadman 200;Perez-Ramirez et al 2019), landscape values (García-Martín et al 2018;Stephenson 2008), ecosystem services (Millennium Ecosystem Assessment 2003) or an embodied perspective, which emphasizes the role of experiences and activities such as recreational uses (Raymond et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The scope of research on this topic has been explored by numerous scientists from different fields (e.g. Altman and Low, 1992;García-Martín, Plieninger and Bieling, 2018;Giuliani, 2003;Gross and Brown, 2008;Huber and Arnberger, 2015;Lu, Lin and Yeh, 2018;Manzo and Perkins, 2006;Prayag and Del Chiappa, 2016;Ramkissoon, Smith and Weiler, 2013;Scannell and Gifford, 2010;Stefaniak, Bilewicz and Lewicka, 2017), and hence it can be defined as highly interdisciplinary. Altman and Low (1992) conducted a study in which they established different research frames rooted in different disciplines.…”
Section: Place Attachmentmentioning
confidence: 99%
“…In contrast, García-Martín, Plieninger and Bieling (2018) learned that place attachment is linked to a desire to participate in making decisions about the local landscape. Within the last two decades, there has been an increasing number of studies on place attachment, with many of them using questionnaires to collect data and produce new knowledge (García-Martín, Plieninger and Bieling, 2018;Huber and Arnberger, 2015;Lu, Lin and Yeh, 2018;Prayag and Ryan, 2012;Stefaniak, Bilewicz and Lewicka, 2017). Over the last few years, there has also been an increase in research on place attachment related to tourism (Gross and Brown, 2008;Lu, Lin and Yeh, 2018;Prayag and Del Chiappa, 2016;Prayag and Ryan, 2012;Ram, Björk and Weidenfeld, 2016;Ramkissoon, Smith and Weiler, 2013;Yuksel, Yuksel and Bilim, 2010).…”
Section: Place Attachmentmentioning
confidence: 99%
“…Since the 90s, studies (Garcia-Martin et al 2018;Valles-Planells et al 2014;Mainardi Peron and Falchero 1994) on the perceptual dimension of landscape and human systems have identified four dimensions of perception: cognitive (related to thought, organization and information), affective (linked to emotions and personal feelings), interpretative (related to the extraction of meaning and the creation of idea associations) and evaluative (linked to values and preferences). According to these studies a mental map can be identified (that is the overall picture each person has made for a landscape and/or a city) which is necessarily partial (unable to understand the whole), simplified (because it omits a lot of information), idiosyncratic (every observer is unique) and distorted (based on distances and subjective directions).…”
Section: Towards a Meta-interpretation Of Energy Systems' Imagementioning
confidence: 99%